2018
DOI: 10.1038/s41467-018-04405-3
|View full text |Cite
|
Sign up to set email alerts
|

Probing the gating mechanism of the mechanosensitive channel Piezo1 with the small molecule Yoda1

Abstract: Piezo proteins are transmembrane ion channels which transduce many forms of mechanical stimuli into electrochemical signals. Their pore, formed by the assembly of three identical subunits, opens by an unknown mechanism. Here, to probe this mechanism, we investigate the interaction of Piezo1 with the small molecule agonist Yoda1. By engineering chimeras between mouse Piezo1 and its Yoda1-insensitive paralog Piezo2, we first identify a minimal protein region required for Yoda1 sensitivity. We next study the effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
122
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(129 citation statements)
references
References 49 publications
(40 reference statements)
6
122
1
Order By: Relevance
“…Therefore, Piezo1 channels may be expressed at low levels, which are undetectable with the antibody used here. As a positive modulator of the Piezo1 ion channel, Yoda1 binds directly to Piezo1 to stabilize the open conformation of the channel pore, thus decreasing the threshold for mechanical activation (Cahalan et al, ; Lacroix, Botello‐Smith, & Luo, ; Syeda et al, ). However, Yoda1 may also exert some off‐target effects, such as increasing the likelihood that other types of Ca 2+ ‐permeable channels will open, as suggested by Dela Paz and Frangos () who showed that Yoda1 activates both Akt and ERK1/2 signaling in endothelial cell types, independent of Piezo1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Piezo1 channels may be expressed at low levels, which are undetectable with the antibody used here. As a positive modulator of the Piezo1 ion channel, Yoda1 binds directly to Piezo1 to stabilize the open conformation of the channel pore, thus decreasing the threshold for mechanical activation (Cahalan et al, ; Lacroix, Botello‐Smith, & Luo, ; Syeda et al, ). However, Yoda1 may also exert some off‐target effects, such as increasing the likelihood that other types of Ca 2+ ‐permeable channels will open, as suggested by Dela Paz and Frangos () who showed that Yoda1 activates both Akt and ERK1/2 signaling in endothelial cell types, independent of Piezo1.…”
Section: Discussionmentioning
confidence: 99%
“…Yoda1 also decreased IL-1β, TNFα, and CX 3 CL1 release from LPS-stimulated astrocytes, suggesting that Piezo1 may play a role in dampening neuroinflammation in the brain. More work is needed to investigate if there is a link between Piezo1-mediated Ca 2+ oscillations, reduced ATP-responsiveness and inhibition of proinflammatory cytokine release from reactive astrocytes [Color figure can be viewed at wileyonlinelibrary.com] Piezo1 to stabilize the open conformation of the channel pore, thus decreasing the threshold for mechanical activation (Cahalan et al, 2015;Lacroix, Botello-Smith, & Luo, 2018;Syeda et al, 2015). However, Yoda1 may also exert some off-target effects, such as increasing the likelihood that other types of Ca 2+ -permeable channels will open, as suggested by Dela Paz and Frangos (2018) who showed that Yoda1 activates both Akt and ERK1/2 signaling in endothelial cell types, independent of Piezo1.…”
Section: Piezo1-mediated Ca 2+ Signaling In Astrocytesmentioning
confidence: 99%
“…Yoda-1 (Tocris, 5586) is a synthetic small molecule that specifically activates Piezo1 at micromolar concentrations (Evans et al, 2018;Syeda et al, 2015) by interacting with the agonist transduction motif of Piezo1 subunits, thus enhancing channel opening-time (Lacroix, Botello-Smith, & Luo, 2018). In contrast to GsMTx4, Yoda-1 may interact directly with Piezo1 domains rather than modifying the lipid environment around the ion channel (Syeda et al, 2015).…”
Section: Reagentsmentioning
confidence: 99%
“…The ability of common inhibitors of mechanosensitive ion channels, namely gadolinium and ruthenium red [10], and the novel Yoda1 antagonist Dooku1 [15], to decrease the Yoda1-evoked Ca 2+ entry in murine and human cardiac fibroblasts correlated with the expected properties of the channel. The mechanism by which Yoda1 modulates Piezo1 activation and gating has been described recently [18]. However, it has also been suggested that Yoda1 may have some Piezo1independent effects in endothelial cells [19].…”
Section: Discussionmentioning
confidence: 99%